2010 IEEE International Frequency Control Symposium 2010
DOI: 10.1109/freq.2010.5556269
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of the phase noise of opto-electronic oscillators based on high quality factor optical resonators

Abstract: Abstract-In order to improve the phase noise of high purity OEO based on optical resonators, like resonant fibre rings, these oscillators have been theoretically studied in terms of white frequency noise. We present here the optimization of the performances of a fibre ring resonator and the experimental phase noise results we obtained for the OEO based on an optimized very high quality factor optical resonator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Thanks to this theoretical study [7], we have designed a new optimized fiber ring resonator of 20m long, using a couplers coupling ratio of 99/1 %. This resonator has been characterized using a measurement set-up described in [5].…”
Section: ) Fiber Ring Resonator Optimization and New Oeo Phase Noise mentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to this theoretical study [7], we have designed a new optimized fiber ring resonator of 20m long, using a couplers coupling ratio of 99/1 %. This resonator has been characterized using a measurement set-up described in [5].…”
Section: ) Fiber Ring Resonator Optimization and New Oeo Phase Noise mentioning
confidence: 99%
“…. The green dashed curve shows the théoretical contribution of the white frequency noise of the 20m-long ring on the OEO phase noise [7] ; measurements are performed on an Agilent E5052B signal source analyser. …”
Section: ) Optoelectronic Oscillatormentioning
confidence: 99%
See 1 more Smart Citation
“…One of our studies has focused on the optimization of the FRR coupling. This has led to find coupling coefficients which realize a trade-off between a high Q Opt and a low noise-to-carrier ratio (NCR) and has resulted in the design of relatively low phase noise FRR OEOs [6]. In addition, the FRR thermal stability has been studied and a FRR and OEO thermal stability of 6.8 ppm K -1 has been found [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the white frequency noise contribution has been evaluated versus κ and an optimized coupling factor of 1% has been finally found to design a new 20m long FRR. The detailed study can be found in [8].…”
Section: B 20m Long Frr With An Optimized Couplingmentioning
confidence: 99%